Self- and team-efficacy beliefs of rowers and their relation to mindfulness and flow - Pineau, T. R.; Glass, C. R.; Kaufman, K. A.; Bernal, D. R. (Journal of Clinical Sport Psychology, 2014)
The present study explored self- and team-efficacy beliefs in rowers, examining the relations between efficacy beliefs, mindfulness, and flow. Fifty-eight rowers from nine teams completed sport-specific measures of self- and team-efficacy, along with questionnaires assessing mindfulness, flow, sport anxiety, and sport confidence. Self- and team-efficacy were significantly related to mindfulness, dispositional flow, and sport confidence. In addition, both self-efficacy and sport confidence mediated the association between both total mindfulness (and the describe dimension of mindfulness) and the challenge-skill balance dimension of flow. These results provide indirect support for a proposed model, which suggests that mindfulness may positively impact the integral challenge-skill balance aspect of flow in athletes through self-efficacy. ABSTRACT FROM AUTHOR